Feasibility and Success of Hiv Point-of-Care Testing in an Emergency Department in an Urban Canadian Setting - Marissa L Becker; Laura H Thompson; Carla Pindera; Natalie Bridger; Carmen Lopez; Yoav Keynan; Jared Bullard; Paul Van Caseele; Ken Kasper (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Approximately 26% of Canadians living with HIV are unaware of their status. Point-of-care (POC) HIV tests have been introduced to simplify and expand HIV testing.